An integrative action research (IAR) on improving the technical onboarding training for new hires before deploying to engagements in internal audit service line - SOX solution - Opinaldo, Mary Grace Q. (Animo Repository, 2022)
The purpose of this insider action research is to improve the technical training for new hires before they will be deployed in the engagement to gain knowledge and skills on SOX testing and SOX proper documentation. My collaborators and I identified a gap in the technical training which is part of the onboarding process for new hires as a whole. Poor onboarding process could lead to different challenges including operational performance and financial impact. Through inquiries, mind mapping, and force field analysis we identified an array of issues and forces that affect the main issue such as efficiency issues, declining productivity, lack of personnel, and etc. Before the intervention, the technical training is only composed of providing video learnings to the new hire, providing only information about the job is found insufficient and ineffective based on reflection of the issue, inquiries, and research. The initiative to improve the process and overall is guided by Lewin’s three-step model. The ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional framework, Effectiveness framework, and different types of inquiries were used to guide us to revisit the process and to establish a robust technical training for new hires. In the first cycle, we focused on analysis and implementation of the training program with consideration of the critical factors that affect the effectiveness of the training. At the end of the first cycle, CIRO Model was used to evaluate the concepts, inputs, reaction, and immediate outcome of the implemented intervention in Cycle 1. Cycle 2 of the project is focused on improving the implemented project through the information gathered from surveys, observation, experiences, and the use of CIRO Model. Further, in Cycle 2 the intermediate outcome of the intervention was evaluated, while the ultimate outcome was not evaluated due to the limitation of the research because it requires a longer period to recognize the outcome. In a broader context, this action research aims to contribute to the knowledge based on the importance and reference of developing a robust technical training for new hires. The action research found that the onboarding technical training to be effective should not only provide job information, but should include knowledge transfer, buddy and counselor relationship, mock audit and knowledge check, and defined evaluation method. These factors mentioned are additions to the critical factors in the Effectiveness Framework used in the research. This action research also suggested a sociotechnical framework which integrates the social aspects to the process that affect the designs and outcome of the intervention. Keywords: Onboarding, Technical Training, Mentoring and Coaching for New Hires, Training Development, New Hires Onboarding, Training Effectiveness, Training Program